Strand 3: Networked learning for professional development: Design and evaluation of technologies to meet learning outcomes - Sharpe, Rhona; Bailey, Paul (Proceedings of the International Conference on Networked Learning, 1998)
Professional development for staff in higher education is developing rapidly in response to current national developments. As staff seek support and development to cope with the changes in their students, appropriate teaching, learning and assessment methods and rising use of learning technologies, institutions must be in a position to provide relevant programmes of development. Increasingly staff will be required to evidence their own development and institutions should be able to offer suitable and accessible systems which allow them to easily document their progress and gain accreditation. As new programmes are being created and existing programmes are evolving quickly in response to these national demands, this paper reminds us of the importance of learning outcomes in design and evaluation. Two case studies which have used learning technologies on professional development programmes are presented. The first case study uses outcomes to redesign the reaching and learning in higher education course for teaching staff to a web based open learning system. The second case study uses the outcomes of a graduate reaching assistants course to evaluate the effectiveness of using a computer conferencing system. The paper intends to give a clear rationale for using learning technologies in professional development programmes and strategies for their design and evaluation. le is hoped that using learning technologies in this way, with the emphasis on outcomes will lead to more appropriate and successful use of technologies for networked professional development.